Ciberumbanda, das epistemes afro-brasileiras às giras digitais nos regimes raciais de informação: encruzilhadas da cosmologia Bantu-Kongo - (:unkn) unknown (INSTITUTO BRASILEIRO DE INFORMAÇÃO EM CIÊNCIA E TECNOLOGIA / UNIVERSIDADE FEDERAL DO RIO DE JANEIRO, 2024)
This research focuses on the visibility of general and specialized sources of information about Umbanda in information regimes. The general objective is to investigate the informational visibility of Umbanda in the digital environment through a critical reading of racial information regimes. It uses qualitative and quantitative methods, with an exploratory-descriptive character, from the collection of data in a digital environment, preliminarily, in Google Trends, Lattes Platform and Reference Database of Journal Articles in Information Science. The research corpus was subsequently constituted from the extraction of data from Youtube Data Tools. The structural theoretical framework came from the bibliographic survey in the Brazilian Digital Library of Theses and Dissertations, in the Library, Information Science & Technology Abstracts with Full Text, in the Institutional Repository of the Institute of Bibliotecological and Information Research of the National Autonomous University of Mexico and in the Web of Science - Clarivate Analytics. Conducts documentary research on the Web, specifically, the website of the Nossa Senhora da Piedade Spiritist Tent. It adopts as an instrument for analyzing the corpus, analytical categories structured from the theoretical framework, by crossing the key concepts of the Pedagogy of the Crossroads (Rufino, 2019) and the minimum characteristics for Afrocentricity (Asante, 2014) in dialogue with Epistemography (García Gutiérrez, 2011) and Transgrammatical Analysis (Saldanha, 2012; 2013), previously used to treat the preliminary data collected in the digital environment. It highlights, in the dialectical discussion of the informational phenomenon of Umbanda, the role of the scientific field and the progress of pseudoscientific eugenicist and evolutionist theses supported by disinformational processes. As an empirical field study, it describes the development of Umbanda in the state of Rio de Janeiro, intertwined with the country's socioeconomic transformations. It reports on police persecutions permitted by the state, seizing material and symbolic artifacts of Afro-Brazilian religions, interfering in the preservation of Umbanda's documentary memory. It discusses the documentary nature of Umbanda's material culture and exposes the strategies of power technologies and the imbrications of the raciality device culminating in the establishment of epistemicide, acting both on black authorship and on its production. It points to the reproduction of racism in the scientific and religious fields and its influence on the flow of the production of this knowledge. It reflects on the mutation of the information regime in the face of constant technological change towards a regime of informational visibility, affecting the cultural and subjective dimensions of subjects, enabling the updating of an informational habitus. It ponders the transformation of the Umbanda terreiro into a cyberterreiro on digital networks as a visibility strategy. It suggests epistemological alternatives established by Brazilian macumbas, through the crystallization of a Eurocentric epistemic model, in meeting the emergency needs of the black population, therefore consistent with the national reality. It shows the Afro-Settled Knowledge Spiral outlined by the precepts of Exu, the orisha of communication, transmitted by Afro-Brazilian religious memory, in an analogy to the Scientific Method Spiral of Shiyali Ramamrita Ranganathan (2009). It presents the Bantu-Kongo Cosmology (Fu-Kiau, 2024), aiming at the adoption of knowledge from this culture, in the composition of the 4 R's of the Informational Crossroads, a model related to the Bantu-Kongo cosmographic model, which seeks to highlight the knowledge intrinsic to the worldview of Afro-Brazilian religions such as Umbanda, with the intention of contributing to credibility and visibility in the public sphere. It assumes that the epistemological turn would be achieved by the transcultural and transversal interconnection of different domains of knowledge, leading to informational balance. The research concludes that there is partial visibility of Umbanda, caused by the production, dissemination and consumption of general information sources about this religion, mainly the YouTube platform, while the scarce production about Umbanda and circulation in specialized information sources in the scientific field, especially in the area of Information Science, contributes to its invisibility in academia and consequently, in information regimes, specifically, racially woven regimes, or, simply, racial information regimes.
Keywords: Umbanda; Ciberumbanda; Epistemologia afro-brasileira; Fontes de informação digital; Regime racial de informação; Ciência da Informação; Cyberumbanda; Afro-brazilian epistemology; Digital information sources; Racial information regime; Information Science; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO